Echocardiographic Investigation of Low-Flow State in a Hispanic/Latino Population - Patrick M. Kozak, MD; Min Pu, MD, PhD; Katrina Swett, MS; Martha L. Daviglus, MD, PhD; Mayank M. Kansal, MD; Daniela Sotres-Alvarez, DrPH; Sonia G. Ponce, MD; Robert Kaplan, PhD; Mario Garcia, MD; Carlos J. Rodriguez, MD, MPH (Mayo Clinic Proceedings: Innovations, Quality & Outcomes, 2022)
Objective: To assess the prevalence of low-flow state (LFS) with left ventricular (LV) stroke volume index of less than 35 mL/m2 and the demographics, clinical and echocardiographic characteristics associated with LV remodeling and function in a Hispanic/Latino population. Participants and Methods: The study included 1346 asymptomatic participants from the Hispanic Community Health Study/Study of Latinos with normal LV ejection fraction (≥55%) and no valvular heart disease. LV volume, mass and left atrial volume, LV ejection fraction, global longitudinal strain, and myocardial contraction fraction were measured by echocardiography. The participants were divided into LFS or normal flow state (NFS: stroke volume index ≥35 mL/m2). Demographics, clinical and echocardiographic characteristics, and measures of LV remodeling and function were compared between the LFS and NFS groups. Results: The prevalence of LFS was 41%. In comparison with NFS, the LFS had lower LV mass index (77.2±0.96 g/m2 vs 84.6±0.86 g/m2; P<.001), left atrial volume index (20.6±0.35 mL/m2 vs 23.5±0.37 mL/m2; P<.001), global longitudinal strain (−16.8±0.16% vs −17.7±0.17%; P<.001), and myocardial contraction fraction (43.3±0.63% vs 55.7±0.64%; P<.001). There was no significant difference in the relative wall thickness (LFS: 0.40±0.004 vs NFS: 0.40±0.005; P=.57). The LFS group had significantly higher hemoglobin A1c (6.18±0.07% vs 5.97±0.04%; P=.01) than the NFS group. Conclusion: A high prevalence of LFS associated with echocardiographic characteristics reflecting unfavorable LV remodeling and function was observed in a Hispanic/Latino population. Further studies of the prognostic significance of LFS in a large multiethnic population are warranted.